Paragraph Writing in Undergraduate English Department: Errors and Its Factors - Latifah Latifah; Umi Hani (UICELL, 2017)
This research was aimed to discuss the errors found in paragraph writing and to explain the factors that caused the problems by the second semester of English students of Fakultas Sastra Universitas Pamulang (UNPAM). Qualitative method was applied in conducting the research in which the data were taken randomly from the paragraphs written by the students. The tools were a paragraph-writing worksheet and a form prepared to record the types of errors of each data. The error category is based on Ferris and Hedgcock model (2005). The errors in the paragraph writing were identified and explained concerning the factors caused the writing problems. Four classifications of errors shown from the result of the writing are: morphological, lexical, syntactic, mechanical error. The four classifications of errors are divided into eight types: noun, article, word choice, sentence structure, subject-verb agreement, spelling, punctuation, and capitalization. It was found that verbs were the highest frequency of errors type.